Global diversity and energy of animals shaping the Earth’s surface - Gemma L. Harvey; Zareena Khan; Lindsey K. Albertson; Martin Coombes; Matthew F. Johnson; Stephen P. Rice; Heather A. Viles (Proceedings of the National Academy of Sciences, 2025)
The collective influence of animals on the processes shaping the Earth’s surface remains largely unknown, with most studies limited to individual species and well-known exemplars. To establish the global geomorphic significance of animals, we systematically reviewed and synthesized evidence across freshwater and terrestrial ecosystems. Over 600 animal taxa had reported geomorphic effects. For the 495 wild animals and 5 livestock identified to species level, we estimated their global abundance, and collective biomass and energy. While our census is global in scope, a lack of research in the tropics and subtropics, and on less visible animals, leaves them underrepresented in analyses. Most reported species are globally widespread, but some are rare, endemic, and/or threatened, leading to risks that key geomorphic processes cease before we fully understand them. We estimate the collective biomass in wild animal geomorphic agents at ≈0.2 Mt Carbon, equating to a biological energy content of ≈7.6 million GJ. If a conservative minimum 1% of this energy contributes to geomorphic work annually, this yields an energy contribution from wild animal geomorphic agents of ≈76,000 GJ—equivalent to the energy of hundreds of thousands of extreme floods. Uncertainties in biomass estimates and energy partitioning mean this value could credibly be an order of magnitude higher, and countless species remain unreported or undiscovered. The livestock estimates exceed the wild animals estimates by three orders of magnitude. The geomorphic energy of animals is far more influential than previously recognized and future losses, dispersal and introductions of zoogeomorphic species may induce substantive landscape changes.